A CuAAC-Hydrazone-CuAAC Trifunctional Scaffold for the Solid-Phase Synthesis of Trimodal Compounds: Possibilities and Limitations - Fabre, Benjamin; Pícha, Jan; Vaněk, Václav; Buděšínský, Miloš; Jiráček, Jiří (Molecules, 2015)
We present a trifunctional scaffold designed for the solid-phase synthesis of trimodal compounds. This scaffold holds two alkyne arms in a free and TIPS-protected form for consecutive CuAAC (copper(I)-catalyzed azide-alkyne cycloaddition), one Fmoc-protected hydrazide arm for reaction with aldehydes, and one carboxylic acid arm with CF₂ groups for attachment to the resin and (19)F-NMR quantification. This scaffold was attached to a resin and derivatized with model azides and aliphatic, electron-rich or electron-poor aromatic aldehydes. We identified several limitations of the scaffold caused by the instability of hydrazones in acidic conditions, in the presence of copper during CuAAC, and when copper accumulated in the resin. We successfully overcame these drawbacks by optimizing synthetic conditions for the derivatization of the scaffold with aromatic aldehydes. Overall, the new trifunctional scaffold combines CuAAC and hydrazone chemistries, offering a broader chemical space for the development of bioactive compounds.
Keywords: Molecular Mimicry; click chemie; Hydrazones; Copper; Polyethylene Glycols; molekulární mimikry; cykloadiční reakce; azidy; Azides; hydrazony; polyethylenglykoly; Click Chemistry; techniky syntézy na pevné fázi; katalýza; měď; Catalysis; Cycloaddition Reaction; Solid-Phase Synthesis Techniques